Availability and use of dry season feed resources on smallholder dairy farms in central Kenya - Nyaata, O.; Dorward, P.; Keatinge, J.D.H.; O'Neill, M. (2000)
A cross-sectional survey on 41 farms followed by six weeks monitoring of dairy cattle feeding on ten smallholder dairy farms in central Kenya was conducted to investigate the use, availability and quality of dry season feed resources. Fodder production was largely from Napier grass (Pennisetum purpureum) grown on small plots and contour strips where it acts both as a fodder source as well as a biological barrier to soil erosion. There is a need to broaden the choice of fodder crops on such farms to provide a wide range of harvesting management options and to avoid total loss in case of pest or disease outbreaks. Intercropping of Napier grass with leguminous fodder trees could boost the quantity and quality of herbage production especially during the dry season. Roughage from a variety of sources was utilised during the dry season in addition to Napier grass. Among the herbages, leguminous feeds had the lowest potential dry matter degradability while weeds harvested from cropland and roadsides had the highest. Energy and protein intake from the roughage fed to grade dairy cattle during the dry season may be insufficient to meet the requirements of these animals due to the high levels of fibre concentration (acid detergent fibre and neutral detergent fibre (ADF and NDF)) in them. It is recommended that the scope for alternative sources of improved roughage such as Napier/calliandra mixtures, to boost the energy, protein and overall dry matter provision on the farms should be investigated further.